Fishers' knowledge and the ecosystem approach to fisheries : applications, experiences and lessons in Latin America (FAO RomeIT, 2015)
Demonstrates the opportunities, constraints and challenges for incorporating fishers' knowledge into fisheries assessment and management in Latin America.
Keywords: FISHERY INDUSTRY